“Desarrollo de un aplicativo móvil para el proceso de venta de productos y servicios tecnológicos aplicando herramientas de inteligencia de negocios en la corporación nacional de emprendedores y telecomunicaciones - CNET del cantón La Maná.” - Chiguano Guamangate, Franklin Isaias (2022)
The National Corporation of Entrepreneurs and Telecommunications (CNET) was The National Corporation of Entrepreneurs and Telecommunications (CNET) was founded on May 11, 2016, located in La Maná Canton of Cotopaxi Province where it began providing computer maintenance services, later in 2019 integrated internet service, and currently offers products such as computers and parts and pc parts, printers, accessories for laptops and desktops, also offers computer technical service, corporate internet plans (businesses organizations), cybers (computer centers) and Home plans (residences, homes). Its main problems are that the company CNET keeps its records (orders, customers, service requests), manually which causes a stack of documents and often loss of information, in the same way, it is unknown what are the best selling products and products with lower demand, the services that are provided more and less requested, therefore it is proposed to develop a mobile application that allows the automation of the sales process of technology products and services, using business intelligence tools in the company CNET, it is important to use methodologies and research techniques that allow collecting information and know-how is the reality of the company CNET as is the case of the unstructured interview can establish a series of questions in advance to the manager of the company to be prepared and that data collection is more efficient, similarly the survey that was established to customers for which a series of specific questions were generated to know your point. For the development, we have used very versatile tools that are booming in software development in the mobile part of the Android Studio development environment, Java programming language, XML design language, and the MariaDB database as a result we obtained one hundred percent functional mobile application, it is possible that in any research project is important bibliographic research as it allows to investigate conclude the best tools to use in the development of software.